THE INFLUENCE OF ACCRUAL EARNINGS MANAGEMENT, REAL EARNINGS MANAGEMENT AND AUDITOR'S REPUTATION ON COMPANY VALUE WITH MODERATION OF CORPORATE GOVERNANCE - Simanjuntak, Megawaty; Mahroji, Mahroji (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
Urgency of this research is because there is still a gap in previous research regarding earnings management and auditor reputation on company value. Novelty in the research by adding the corporate governance mechanism factor as a moderating variable which was not investigated in previous research. This research aims to test the effectaccrualsearnings management, real earnings management,and auditor's reputation on firm value with corporate governance as moderator. The research sample used was 133 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The method of determining the sample using a purposive technique with reference to several established criteria. The data analysis method uses panel data regression through the approachGeneralizedMoment of Methode(GMM). The results showed that accruals and real earnings management had a negative effect on firm value, while auditor reputation had a positive effect on firm value. Apart from that, research also shows that corporate governance is able to weaken the influence of accrual and real earnings management on company value, and strengthen the influence of auditor reputation on company value. This research raises managerial contributions for companies to further improve corporate governance through the implementation of the ACGS scorecard in providing transparency and accountability to stakeholders. Keywords: accrualsearnings management, real earnings management, auditor reputation corporate governance, company values..